2008
DOI: 10.1097/pec.0b013e31816b7aa4
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spinal Cord Injury in Abused Children

Abstract: Five infants and toddlers who sustained cervical spinal cord injury as the result of child abuse are described. Three cases are previously unreported. Diagnosis was complicated by coexistent brain injuries and their treatments, subtle and/or evolving paralysis, and central cord syndrome, in which arm function is diminished but leg function is preserved. Definitive spinal imaging by magnetic resonance imaging (MRI), computed tomography, and plain radiographs was delayed because of life support efforts. When com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 29 publications
0
28
1
Order By: Relevance
“…2 A small case series notes that cervical spine injury in child abuse likely is rare and, when present, diagnosis may be delayed. 7 The mortality rate for children with cervical spine injury ranges from 13% to 28%. 2,5,8 Mortality is highest in younger patients and those with higher cervical spine injuries.…”
mentioning
confidence: 99%
“…2 A small case series notes that cervical spine injury in child abuse likely is rare and, when present, diagnosis may be delayed. 7 The mortality rate for children with cervical spine injury ranges from 13% to 28%. 2,5,8 Mortality is highest in younger patients and those with higher cervical spine injuries.…”
mentioning
confidence: 99%
“…We included 19 small case series or case studies, published between 1975 and February 2009, representing 25 children who had sustained inflicted spinal injury 8 11 1430. All studies ranked 1–2 for abuse, confirmed by communication with authors in two studies 28 30.…”
Section: Resultsmentioning
confidence: 99%
“…Population studies estimate that 3–8% of spinal injuries are the result of child abuse7; however, it is difficult to quantify the true scale of the problem, as many studies do not appear to consider inflicted injury as a possible cause. Studies of children who have been physically abused estimate that 1% of children who suffer abusive head trauma have coexisting spinal trauma,8 and between 1% and 3% of abusive fractures are to the vertebrae 9 10…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive reviews have found that 1%-3% of abusive fractures involved the vertebrae and that 1% of children who suffer abusive head trauma have coexisting spinal trauma [7,8,15,16]. Few data are available with respect to the hands and feet, but limited reports suggest that these injuries are also very uncommonly noted on skeletal surveys [3,14,17].…”
Section: Discussionmentioning
confidence: 99%